Low Micronutrient Adequacy And Rising Overweight And Obesity Among Ready-made Garment Workers In Bangladesh - Afrin, Shazia; Alam, Md Mahbub; Sarwar, Sneha; Hossain, Md Shahadoth; Sumon, G M Reza; Shaheen, Nazma; Amin, Md Ruhul; Mahbub, Md Jarif (Bioresearch Communications, 2024)
Background/Objective: The ready-made garment (RMG) sector is key to Bangladesh's economy, significantly contributing to GDP and foreign exchange earnings. However, RMG workers, predominantly women, face critical challenges related to health, nutrition, and productivity. Despite their socio-economic importance, research on their diet quality, nutrient adequacy, and nutritional status remains limited. This study aimed to assess the dietary quality, probability of nutrient adequacy, and nutritional status of RMG workers in Bangladesh. Methodology: A cross-sectional study was conducted among 801 RMG workers (333 males and 468 females) employed in two garment industries in Dhaka and Mymensingh. Participants were selected using convenience sampling. Data on socio-demographics, dietary intake, and anthropometry were collected, and nutritional status was assessed using BMI classifications from both WHO and Asian standards. Micronutrient adequacy was evaluated using the probability approach (PA), incorporating estimated average requirement (EAR) values and standard deviations. Descriptive and inferential statistical methods were employed. Multiple logistic regression was used to investigate the influence of socioeconomic factors on workers' micronutrient adequacy. Results: Among the 801 RMG workers studied, 58.4% were female, and 90.3% were aged 18-34. Macronutrient distribution indicated excessive carbohydrate intake (67.0% of total energy), while fat intake was often below ideal levels in 43.4% of participants (<15% of total energy). More than half of the RMG workers exhibited inadequate micronutrient intake, with a mean micronutrient adequacy (MPA) score below 0.5. The MPA of micronutrients was significantly higher for RMG workers in Mymensingh (AOR 1.68, p = 0.004) and those aged 25-34 (AOR 1.40, p = 0.049). Calcium consumption among RMG workers was alarmingly low, with most consuming less than 50% of the Estimated Average Requirement (EAR). Similarly, intakes of iron, zinc, riboflavin, and vitamin A were at or below the EAR, indicating a high risk of inadequacies. A concerning overnutrition was observed, with 44% overweight or obese based on Asian BMI standards while it was 24.1% based on WHO BMI standards, with a higher prevalence observed among female workers. Conclusion: The study findings highlight the coexistence of overnutrition and micronutrient inadequacy among RMG workers. Targeted nutritional interventions, such as establishing fair-price shops and promoting nutrition education, are recommended to improve food affordability, encourage healthier dietary practices, and enhance workforce productivity. Bioresearch Commu. 11(1): 1728-1740, 2025 (January)